2009
DOI: 10.1063/1.3168442
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical properties of infrared-emitting YF3:Nd nanoparticles

Abstract: Nd 3 + -doped YF3 (YF3:Nd) nanoparticles with a size of ∼20 nm were synthesized by solvothermal decomposition of yttrium and neodymium trifluoroacetate precursors in oleylamine. Using the 4f-energy matrix diagonalization procedure various interaction parameters: Slater–Condon (F2, F4, and F6), spin-orbit (ξ), two body interaction (α, β, and γ), Judd parameters (T2, T3, T4, T6, T7, and T8), spin-other-orbit parameters (M0, M2, and M4) and electrostatically correlated spin-orbit interaction parameters (P2, P4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 36 publications
5
69
0
Order By: Relevance
“…It is known that the Nd 3 + quantum effi ciency increases as the Nd doping concentration is decreased. [ 33 ] We fi nd that 0.5% Nd doped LaF 3 is optimal taking into consideration both quantum yield and brightness.…”
Section: Doi: 101002/adma201104769mentioning
confidence: 85%
“…It is known that the Nd 3 + quantum effi ciency increases as the Nd doping concentration is decreased. [ 33 ] We fi nd that 0.5% Nd doped LaF 3 is optimal taking into consideration both quantum yield and brightness.…”
Section: Doi: 101002/adma201104769mentioning
confidence: 85%
“…The solvothermal synthesis method has been used to grow various rare-earth doped particles with controlled micron- to nano-sizes and morphologies by adjusting the reaction parameters, like precursor concentration, time and solvent. 29, 37, 39, 41, 42, 45, 47, 4952 For example, the thermal decomposition of rare earth trifluoroacetate precursors in solvents such as oleic acid or oleylamine under temperatures 250–350°C is commonly used to synthesize crystalline monodisperse REs of tailored size. 42, 53, 45 …”
Section: Rare Earth Nanoprobesmentioning
confidence: 99%
“…For example, the hydrocarbon (-CH 2 ) and hydroxyl (-OH) groups present on surfactants used during synthesis can deactivate surface rare-earth ions on REs and result in emission quenching. 41 We have previously investigated the effects various surfactant formulations have on RE emission using micron-sized particles. NaYF 4 :Yb-Er were synthesized using the hydrothermal method and subsequently modified with low concentrations of different surfactants.…”
Section: Rare Earth Nanoprobesmentioning
confidence: 99%
“…These probes emit shortwave infrared (SWIR) light upon excitation by NIR light (980 nm), which has several advantageous properties, including deeper penetration through biological tissue, for biological imaging. 1719 Additionally, the absence of excitation–emission band overlap and elimination of tissue autofluorescence produces significantly improved signal-to-noise ratios. We have previously shown that RENPs can be rendered biologically safe by encapsulation in albumin nanocomposites 15 and can be targeted for the detection of micrometastatic lesions in multiple organs.…”
Section: Introductionmentioning
confidence: 99%